Academic Stress and Physical Activity in Adolescents - Frömel, Karel; Šafář, Michal; Jakubec, Lukáš; Groffik, Dorota; Žatka, Radim (BioMed research international, 2020)
The issue of work-related mental health needs to be addressed at the school level. The aim of this study was to explore the associations between academic stress (AS) of adolescent boys and girls and their physical activity (PA) during recesses and after school and to propose measures to promote the adoption of lifelong healthy working habits. Adolescents from 16 schools in the Czech Republic and 6 schools in Poland participated in the study (187 boys and 339 girls). Monitoring of PA and cognitive stress was conducted during one school day. We used ActiTrainer accelerometers to monitor PA and physical inactivity. Data on time of PA and self-reported AS in school lessons were collected using recording sheets. We split the participants into two groups: those without a self-reported stressor and those who indicated one or more stressors. Differences in overall PA during recesses, as well as after-school PA, between boys with and without AS were not statistically significant for any PA characteristics. We observed similar results for girls. Repeated measures ANOVA confirmed that differences in PA (steps/hour) during recesses following particular lessons between participants with and without AS were not statistically significant in boys or girls (F (4,1612) = 1.83, p=0.121 , η p 2=0.005). It is noteworthy that girls with AS were statistically significantly more likely to meet the 6000 steps after school time recommendation (39%) than girls without AS (18%; p < 0.001). The study did not confirm the assumption that adolescents reporting AS have less PA during recesses or even after school than adolescents without AS. However, the overall low PA of adolescents during recesses and after school highlights the need to compensate for AS by adequate PA. This is especially true for adolescents with recurrent AS in several consecutive lessons.
Keywords: pohybová aktivita; Humans; studenti; Female; Polsko; lidé; Poland; Stress, Psychological; ženské pohlaví; Male; Adolescent; Czech Republic; psychický stres; Motor Activity; Exercise; Students; Česká republika; mužské pohlaví; cvičení; mladiství